2006
DOI: 10.1074/jbc.m512082200
|View full text |Cite
|
Sign up to set email alerts
|

Murine Thrombin Lacks Na+ Activation but Retains High Catalytic Activity

Abstract: Human thrombin utilizes Na؉ as a driving force for the cleavage of substrates mediating its procoagulant, prothrombotic, and signaling functions. Murine thrombin has Asp-222 in the Na ؉ binding site of the human enzyme replaced by Lys. The charge reversal substitution abrogates Na ؉ activation, which is partially restored with the K222D mutation, and ensures high activity even in the absence of Na ؉ . This property makes the murine enzyme more resistant to Thrombin is a Na ϩ -activated serine protease (1) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 61 publications
0
57
0
Order By: Relevance
“…Activity toward this substrate is also compromised due to increased K m and reduced binding but without the increase in k cat observed for FPR. Finally, the chymotrypsin-specific substrate FPF, for which thrombin shows considerable activity unlike trypsin (27), experiences only a modest drop in k cat /K m in the slow form and a more pronounced drop in the fast form. The limited solubility of this substrate prevents independent assessment of the indi- vidual Michaelis-Menten parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Activity toward this substrate is also compromised due to increased K m and reduced binding but without the increase in k cat observed for FPR. Finally, the chymotrypsin-specific substrate FPF, for which thrombin shows considerable activity unlike trypsin (27), experiences only a modest drop in k cat /K m in the slow form and a more pronounced drop in the fast form. The limited solubility of this substrate prevents independent assessment of the indi- vidual Michaelis-Menten parameters.…”
Section: Resultsmentioning
confidence: 99%
“…If E* is indeed an inactive conformation of thrombin (47,52), then the recent structure of the mutant D102N in the free form offers a possible representation (42). Given the current structural assignments of E*, E, and E:Na ϩ , one can conclude that the structural changes in the 60-loop documented upon PAR3 binding to exosite I of murine thrombin (32) pertain to a conformation of the enzyme that is stabilized in the highly active E:Na ϩ form (53,54). In fact, murine thrombin is constitutively stabilized in the E:Na ϩ form by the D222K replacement in the Na ϩ site, where Lys-222 provides molecular mimicry of the bound Na ϩ (54).…”
Section: Discussionmentioning
confidence: 99%
“…Construction of a thrombin-like protease could focus on either the pro-or anti-coagulant state of the enzyme, yet must rely on the allosteric network responsible for Na þ activation. Recent studies on murine thrombin have demonstrated that thrombin may be locked into the Na þ -bound state by using the Nz atom of K222 as an internal monovalent cation (18). Further engineering of exosite I would be necessary to introduce the fibrinogen recognition site.…”
Section: Paolo Ascenzimentioning
confidence: 99%